2022
DOI: 10.1007/s40670-022-01580-3
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Medical Students Before and During COVID-19 Pandemic: a 3-Year Prospective Study

Abstract: Background Very few studies prospectively analyzed medical students’ mental health before and during the COVID-19 pandemic. This study aimed to prospectively evaluate mental health in medical students in 2018, 2019, and 2020 during the COVID-19 pandemic lockdown. Methods All students from first to fourth year were invited to participate in 2018. These students were also invited to participate in the same period in 2019 and 2020 (during the peak of the COVID-19 lockdown)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Regarding mental health issues, the results show a risk of MMD in 55.5% of the total number of students. The result is similar to data from other medical schools, which show percentages from 60.5 to 29.6% ( Conceição et al, 2019 ; Melado et al, 2019 ; Prata et al, 2021 ; Pereira et al, 2022 ). Despite the variable percentages, systematic reviews point to greater fragility in the mental health of medical students compared to the general population ( Oliveira and Araujo, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…Regarding mental health issues, the results show a risk of MMD in 55.5% of the total number of students. The result is similar to data from other medical schools, which show percentages from 60.5 to 29.6% ( Conceição et al, 2019 ; Melado et al, 2019 ; Prata et al, 2021 ; Pereira et al, 2022 ). Despite the variable percentages, systematic reviews point to greater fragility in the mental health of medical students compared to the general population ( Oliveira and Araujo, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…A study conducted among US medical students showed that, compared to previous data during the COVID-19 era, anxiety and depression were 61 and 70% higher, respectively (Halperin et al, 2021). In comparison, a prospective study from Brazil showed stability in the medical students' mental health (Pereira et al, 2022).…”
Section: Coronavirus Disease-caused Online Learning and Mental Healthmentioning
confidence: 92%
“…Previous research conducted in April 2020 indicated a decreasing prevalence and level of burnout, depression, anxiety, and somatic symptoms after transitioning to OL (Bolatov et al, 2021a). However, this study was conducted in the early stages of a pandemic and therefore has several limitations (Pereira et al, 2022). Moreover, there is a need for more information on the long-term effects of the COVID-19 pandemic on medical students and their education (Žuljević et al, 2021).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The general questionnaire included data on age, grade, gender, family situation, academic performance, major life events, and other social demographic data. Using the symptom self-rating scale (SCL-90)[ 8 , 9 ], a total of 90 items were scored at 5 levels (0-4), with scores ranging from 0 (none) to 4 (severe); the scale is divided into physical status, interpersonal sensitivity, obsessive-compulsive symptoms, anxiety, depression, hostility, paranoia, terror, psychosis and another 10 symptoms. This scale is commonly used in mental health screening tools due to its comprehensiveness and ease of understanding.…”
Section: Methodsmentioning
confidence: 99%